Pengaruh Rotasi Kerja, Quality Of Worklife dan Gaya Kepemimpinan Transformasional terhadap Kinerja Karyawan pada PT. PLN(Persero) Wilayah Sumatera Utara - Mutholib Mutholib; Baihaqi Ammy (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2020)
The purpose of this study was to analyze the effect of work rotation on employee performance, to test and analyze the quality of work life on performance; To test and analyze the transformational leadership style of employee performance; To test and analyze work rotation, quality of work life and transformational leadership style together on employee performance at PT. PLN (Persero) North Sumatra Region. The approach used in this research is an associative approach. The population in this study were all employees at PT. PLN (Persero) Wilayah Sumatra Utara, the population in this study was 71 employees. The researcher will examine the entire population, so that the research sample is population data (census study). Data collection techniques in this study using primary data. Data analysis techniques in this study using multiple linear regression analysis. The results showed all independent variables partially and simultaneously significant effect on employee performance at PT. PLN (Persero) North Sumatra Region.